Rethinking structures of tales as old as time : transformation of genre across adaptations of "beauty and the beast" and howl's moving castle - Maliah Zubir (2018)
This paper aims to investigate the transformation of the form of fairy tales through the centuries with focus on “Beauty and the Beast”, a tale of transformation in itself. By examining adaptations of “Beauty and the Beast”, I am proposing a framework which discusses the formal aspects that define a genre, and how adaptations can expose the liberations and limitations of a genre. With special attention to film aesthetics, I will illustrate how fluidity of transformation in Howl’s Moving Castle reflects fluidity of the fantasy genre itself in comparison to the fairy tale genre.